2014
DOI: 10.1002/oby.20908
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index with lifestyle and rotating shift work in Japanese female nurses

Abstract: Objective: Higher body mass index (BMI) values have been reported in rotating shift workers compared with regular daytime workers. This study examines the relationship between work schedule and BMI, and considers whether lifestyle habits could explain the relationship. Methods: Japanese female nurses (1179 day workers and 1579 rotating shift workers, aged 20-59) were studied using self-administered questionnaires. The questionnaires assessed height, weight, and dietary intake, physical activity, and sleep (lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
116
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 18 publications
1
116
1
2
Order By: Relevance
“…In contrast to our finding of a higher energy intake among shift compared to day workers, the majority of previous studies observed no significant differences (15,17,19,24,39,40). However, three of these studies observed a statistically non-significantly higher energy intake among shift compared to day workers (24,39,40).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our finding of a higher energy intake among shift compared to day workers, the majority of previous studies observed no significant differences (15,17,19,24,39,40). However, three of these studies observed a statistically non-significantly higher energy intake among shift compared to day workers (24,39,40).…”
Section: Discussioncontrasting
confidence: 99%
“…During irregular shifts, shift workers tend to eat a larger number Shift work and diet of small meals and eat more at irregular times (13,14). As to their usual diet, shift workers seem to consume more high-energy snacks and sugars than day workers (14)(15)(16)(17). Shift workers were also found to have a lower intake of fruits and vegetables (17,18), fiber (19) and some vitamins and minerals (eg, vitamin B, C, magnesium) (19) than day workers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The costs associated with poor sleep, unhealthy lifestyle behaviours and obesity extend beyond the worksite organization and negatively affect the individual and society. Numerous studies have reported on negative changes in sleep quality in employees working rotating or night shifts [21][22][23]. Further, employees working night shift may exhibit differences in lifestyle habits, such as increased sugar-sweetened beverage consumption [22], higher caloric intake and smoking status [23] which in turn is associated with increased BMI, [22,24,25] and elevated chronic disease risk [23].…”
mentioning
confidence: 99%